A Study on Consumers’ Perceived Value and Satisfaction with Insecticides Used in Paddy in Jorhat District of Assam - Bhagat, Deepak; Barooah, B. K. (Indian Journal of Marketing, 2010)
The agrochemical industry in general is a seasonal industry and since it is connected to agricultural production, it is a core industry in India. For agriculture to be commercially viable, with various other inputs, it requires certain key agrochemicals and pesticides are one of them. A perusal of the table 1 depicts that average pesticide consumption in India over a period of 1991 to 2007 was 51.79 thousand tones. Though compound growth rate (CGR) shows a negative growth rate, it cannot be denied that on the demand side, farmers were concerned that their larger and more frequent harvests would draw insect pests. This fright, along with influential marketing by pesticide producers, led farmers to spray ever-increasing quantities of these chemicals on their crops. Anticipating the importance and opportunity, a number of players entered into the market. Among the multinationals, there are Bayer Crop Sciences, Syngenta, De-Nocil, Monsanto, BASF’s agro division, Dupont’s agrochemical division and Cheminova. In the domestic players - United Phosphorus, Exel Industries, Rallis, Gharda Chemicals, Sabero, Nagarjuna Agrichem and Indofil are the main players. Though there are MNCs and domestic players in the industry, there is no such difference in quality of products manufactured by them. It is more a question of product range.